Leucoplasias bucais: estudo comparativo entre o grau histológico de displasia, imunoexpressão de hMLH1 e p53 e análise quantitativa de AgNOR - Patrícia Carlos Caldeira (2010)
hMLH1 is a protein of the mammalian mismatch repair system (MMR), which maintains genomic stability during repeated duplication. Investigations point to a role of hMLH1 in oral carcinogenesis, and its expression pattern may be related to epigenetic events and microsatelliteinstability in oral leukoplakias and squamous cell carcinomas. It seems that those alterations are related to the histological severity of these lesions. It has been suggested that the MMR machinery could activate and be linked to regulation of p53, a tumor supressor protein which iscommonly altered in human cancers. The AgNOR technique is used to assess the cell proliferation. This study aimed to assess and to compare the immunoexpression of hMLH1 and p53, and the AgNOR number, in oral leukoplakias with different degrees of epithelial dysplasia.Sixty-two specimens of oral leukoplakia were classified into four groups: 17 without dysplasia, 19 with mild dysplasia, 16 with moderate dysplasia, and 10 with severe dysplasia. Immunohistochemistry for hMLH1 and p53, and AgNOR technique were performed. Results are shown as percentage of immunopositive cells and mean AgNOR number and statistical analysis was made. Decreasement in hMLH1 and increasement in p53 and AgNOR indexes were observed throughout the development of more severe dysplasia, despite statistical significance.Considering oral leukoplakia groups, indexes of hMLH1 expression in suprabasal and all layers were statistically significant for all comparisons except for oral leukoplakia with moderate and severe dysplasia. An inverse correlation between hMLH1 and both p53 and AgNOR, and a direct correlation between p53 and AgNOR could be observed. Ou results suggest that during the development of more dysplastic phenotypes in oral leukoplakias, keratinocytes seem to present diminished capacity of DNA repair and tumor supression, indicating that these alterations couldbe early events in oral cacinogenesis. These pathways can be somehow interconected, as well as the increasement in cellular proliferation